Knee joint measurement using CT scans for knee joint implant selection - Jing, Mei (2009)
The surgical process of knee joint replacement is called a Total Knee Arthroplasty (TKA). This surgery involves replacing your knee joint with an artificial one. During the operation, once the knee joint is opened, surgeons will place a special positioning device (a cutting guide) on the end of the femur. This cutting guide is for ensuring the bone is cut in the proper alignment to the leg's original angles, even if the arthritis has made the patient bowlegged or knock-kneed. With the help of the cutting guide, the surgeon cuts several pieces of bone from the end of the femur in order to match the implant shape, that’s called shaping the distal femoral bone. Then surgeons will place several different sizes of implant on it in order to find out the best fit one. (1) The objective of this project is to develop an efficient way to find out the suitable size of implant using CT scans or photo taking, to measure anterior-posterior and media-lateral lengths of the knee joint. This project was done in collaboration with surgeons and research scientists from SGH (Singapore General Hospital) to facilitate knee joint replacement surgery procedure. MATLAB was employed for CT image processing. The maximum anterior-posterior and media-lateral length of femur (before surgical shaping) can be detected by running this MATLAB program.